Examining Inter-organizational Network During Emergency Response of Gunungkidul Drought 2019 - Agung Wicaksono (Policy & Governance Review, 2020)
Drought is a disaster that often occurs in Gunungkidul Regency, where the condition was exacerbated by the occurrence of a long drought in 2019 (BMKG, 2019). Beside climatic and geological factors, drought is also caused by the involvement of multi-stakeholders, including local governments in managing drought emergency conditions. This research presented a case study on drought disaster management in Gunungkidul in 2019, where qualitative and social network analysis research methods were applied. Social network analysis was used to examine the central actors of the organizations involved in drought management and the role of networks in these levels of government. Meanwhile, qualitative methods were used to explore the factors influencing the network. The results show that the central actors during the emergency response were BPBD, PMI, and PDAM of Gunungkidul Regency. Meanwhile, the role of inter-organizational networks at the district level had been optimized by performing command and control over developments in the situation, involving community organizations and business institutions. Furthermore, on the factors affecting the network, everything had been maximized except two factors that were still lacking, including partnerships and the use of sophisticated information technology.